The Communicative Unveiling: Bridging Reputation and Reality through Dialogue in Islamic Campus Accreditation - Sazali, Hasan; Ritonga, Hasnun Jauhari; Matondang, Abdul Rahman (MUHARRIK: Jurnal Dakwah dan Sosial, 2023)
This study investigates organizational communication's role in achieving superior accreditation at the State Islamic University of North Sumatra (UIN-SU). The research method used is mixed, with a survey-based quantitative approach using questionnaires to collect data from UIN-SU students, lecturers, and teaching staff and a qualitative approach through interviews with universities that have achieved superior accreditation. Data were analyzed using statistical analysis techniques and path analysis with moderating variables. The results showed that UIN-SU achieved a "B" (Superior) accreditation rating, which reflects a commitment to improving the quality of higher education services. The effectiveness of internal communication and the quality of external communication played a crucial role in achieving this feat. However, the participation of academic community members in decision-making did not have a significant impact, indicating the need to increase their participation and role in the accreditation process. In order to achieve higher accreditation in the future, UIN-SU needs to focus on improving organizational communication, supportive organizational policies and culture, and allocating adequate resources to support accreditation efforts and improve the quality of higher education.